The state and the economic recovery - JELEV, Viorica (Annals of Spiru Haret University. Economic Series, 2010)
World economy undergoes the century’s most serious crisis. At the same time, worldwide population is facing the food and energy crises, the climate change, poverty and a strong economic outlook uncertainty. Several developed countries feel the recession effects, while developing countries record lower development assistance levels. This trend may impact considerably those vulnerable and marginalized groups, especially women (according to the World Bank’s programmes). On this background, the state must have an active role; the decisions to be further made by the European leaders at micro and macroeconomic level will affect the worldwide population.